Mechanisms underlying the wound healing and tissue regeneration properties of a novel gauze dressing impregnated with traditional herbal medicine (Ya-Samarn-Phlae) in type 2 diabetic Goto-Kakizaki (GK) rats - Sanpinit, Sineenart; Issuriya, Acharaporn; Sakulkeo, Oraphan; Wetchakul, Palika; Limsuwan, Surasak; Na-Phatthalung, Pinanong; Kantisin, Siriwan; Tang, Jian; Chusri, Sasitorn (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceA traditional preparation of Ya-Samarn-Phlae (T-YaSP) consists of Garcinia mangostana L., Oryza sativa L., Curcuma longa L., and Areca catechu L. and has been used in Thai medicine as an infused oil for treating chronic and diabetic wounds. It is reputed for its antibacterial, antioxidant, and wound-healing properties. Despite its traditional use, scientific validation of the mechanisms underlying diabetic wound healing remains limited.AimThis study aims to develop a novel gauze dressing impregnated with an ointment containing T-YaSP (YaSP) to enhance its practical application and elucidate the mechanisms of action in promoting wound healing in both non-diabetic and type 2 diabetic wounds of this ointment.Materials and methodsYaSP was developed and tested for stability and dermal irritation. Changes in chemical markers during storage were measured both qualitatively and quantitatively. Its anti-inflammatory activity was assessed using the carrageenan-induced rat paw edema model. The effect of YaSP on levels of nitric oxide (NO), myeloperoxidase (MPO), malondialdehyde (MDA), inflammatory cytokines (TNF-α, IL-1β, and PGE2), and pro-inflammatory enzymes (iNOS and COX-2) was measured. The wound-healing effects of YaSP were assessed using full-thickness (6 mm diameter) wound models in both non-diabetic Wistar rats and type 2 diabetic Goto-Kakizaki rats. In addition to evaluating wound closure on days 0, 3, 5, 7, 9, and 11, the influence on TGF-β1, VEGF, and the production of collagen types I and III, which indicate the inflammatory, proliferative, and remodeling phases, was measured.ResultsDuring the 6-month storage period, the α-mangostin content measured in YaSP did not decrease; however, the curcumin level showed a significant reduction. Topical treatment with YaSP demonstrated strong anti-inflammatory activity and alleviated oxidative stress and inflammatory markers. YaSP improved wound closure rates in both diabetic and non-diabetic models. Levels of TGF-β1 and VEGF increased, indicating the promotion of angiogenesis and granulation tissue formation during the proliferation phase on the seventh day. Additionally, TGF-β1 levels dropped on the 11th day, aligning with diminished inflammation and enhanced remodeling. The treatment balanced collagen synthesis, increasing type III collagen in the early stages and type I collagen in the later stages of wound healing. Histological analysis confirmed reduced inflammation, enhanced neovascularization, and increased collagen production.ConclusionA gauze dressing impregnated with YaSP provides a practical solution for diabetic wound management and demonstrates strong wound-healing properties by modulating excess inflammation, promoting angiogenesis during the proliferation phase, and regulating collagen synthesis throughout the remodeling phase. This discovery reveals, for the first time, the underlying mechanisms of action of this traditional formulation, highlighting its potential as a cost-effective alternative for managing chronic wounds in resource-limited settings.